The Predictive Power of Stock Market Indicators - Branch, Ben (Journal of Financial and Quantitative Analysis, 1976)
Empirical research has cast so much doubt on chart readers that most capital theorists have about as much faith in charts as astronomers have in astrology. Certainly there is overwhelming evidence that attempting to predict future price changes on the basis of past price behavior is unproductive. There is, however, another aspect of technical analysis which has received much less attention from academicians. In its narrow form technical analysis seeks to forecast the direction of price movements of individual securities from past price and volume data. A second and somewhat broader type of technical analysis concentrates on the prediction of general market movements and trends relying on a broader set of information. Various market indicators are said to offer signals useful in forecasting future prices. One type seeks to measure investor sentiment through what might be called mood variables. A second type of indicator is more closely related to fundamental factors affecting future supply and demand for securities. Both types of indicators, however, are designed to be used in predicting future market movements rather than the movements of individual stock prices. This is to be contrasted with fundamental analysis which is concerned with predicting future prices of individual securities by analyzing the underlying factors related to the firm's future profitability. Most of the prior work with market indicators takes one or another proposed market indicator and examines the historical relation, between the indicator and some market index such as the Dow Jones Industrial Average.